Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

solve for c
14 + (–12) = –12 + c

solve for k
–(k + 12) = 6 + (–12)

(two questions)


Sagot :

solve for c
add like terms
get 2 = c - 12 then add 12 to both sides
+12 +12
so c = 14


solve for k
first distribute and add like terms
-k - 12 = -6 add 12 to both sides
get -k = 6 multiply both sides by -1
k = -6